2022
DOI: 10.1155/2022/2471039
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Effect Evaluation of Bronchial Artery Embolization for Hemoptysis of Lung Cancer and Changes in Serum Tumor Markers and miR‐34 Levels

Abstract: The clinical efficacy, serum tumor markers, and miR-34 expression levels of bronchial artery embolization (BAE) in patients with lung cancer with hemoptysis are investigated. 92 patients with lung cancer hemoptysis treated in our hospital from January 2019 to December 2021 are randomly selected, and 92 patients are randomly divided into the conservative group and the BAE group according to the number table method, with 46 patients in each group. The efficacy, overall survival (OS) rate, coagulation function, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This dual effect renders BACE more advantageous than systemic chemotherapy and BAI alone due to its better therapeutic efficacy without the concomitant increase in treatment-related adverse effects ( 26 ). Even in chemotherapy-insensitive recurrent lung cancer, mechanical embolization of the bronchial arteries alone is equally effective ( 27 ). Theoretically, BACE can be performed in all types of lung cancer, and may be useful as long as the blood supply vessels are present, without the need for other relevant tests.…”
Section: Discussionmentioning
confidence: 99%
“…This dual effect renders BACE more advantageous than systemic chemotherapy and BAI alone due to its better therapeutic efficacy without the concomitant increase in treatment-related adverse effects ( 26 ). Even in chemotherapy-insensitive recurrent lung cancer, mechanical embolization of the bronchial arteries alone is equally effective ( 27 ). Theoretically, BACE can be performed in all types of lung cancer, and may be useful as long as the blood supply vessels are present, without the need for other relevant tests.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%